The effectiveness of inhaled ginger essential oil in improving dietary intake in breast-cancer patients experiencing chemotherapy-induced nausea and vomiting - Zakaria, Noor Salihah; Mamat, Nik Mazlan; Lua, Pei Lin (Royal Pharmaceutical Society, 2016)
Background: Evidence suggests the use of complementary therapies may help in relieving the adverse effects of cancer-related treatment, including nausea. Objectives: To evaluate the effectiveness of inhaled ginger essential oil (EO) in improving dietary intake in women with breast cancer experiencing chemotherapy-induced nausea and vomiting (CINV). General perception on the use of ginger aromatherapy was also evaluated. Methods: A single-blind, randomised, placebo-controlled, crossover study was conducted in two oncology clinics in Peninsular Malaysia. Women received 5 days of aromatherapy treatment using either ginger EO or fragrance-matched placebo [ginger fragrance oil (FO)] in an order dictated by the treatment group sequence. The following aspects were evaluated: nutritional status (BMI, nutritional requirement, dietary intake) and general perception of aromatherapy. Results: Sixty women completed the study (age=47.3 +/- 9.26 years; receiving highly emetogenic chemotherapy=86.7%; BMI=25.5 +/- 5.4 kg/m2). Energy intakes were significantly higher after patients were treated with ginger EO than ginger FO at day 3 (P=0.015) and day 5 (P=0.002). Significant improvements in energy intake were also observed over time [F(2,57)=54.21, P<0.001], reaching almost 90% of the energy requirement 5 days’ post-chemotherapy. Inhaled aromatherapy using ginger EO was rated marginally more helpful than the ginger FO (63.3% vs. 61.6%). Being delivered via a necklace, the treatment method was considered feasible for participating women. Conclusion: The use of inhaled ginger EO for CINV could possibly help patients resume their dietary intake. This complementary treatment was also favourably received by the participating women.